2020
DOI: 10.1002/admi.202001231
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Limited Ice Formation and Efficient De‐Icing on Superhydrophobic Micro‐Structured Airfoils through Direct Laser Interference Patterning

Abstract: Surface contamination by ice poses a hazard to industries ranging from power transmission to transportation by ground, sea and air. The aviation industry is particularly affected by icing phenomena that manifest as a reduction in fuel efficiency and compromised aerodynamic lift, which can impair flight safety. [1] Consequently, there is a worldwide scientific effort to understand the physics of icing, aiming to develop effective and efficient anti-icing and de-icing strategies. [2] Icing can occur while aircra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…A novel approach to target these objectives are micro-textured functional surfaces with icephobic properties. An icephobic surface has per definition the following properties: (i) they delay the solidification time of the water or reduce ice accretion while the heterogeneous nucleation is hindered [ 20 ] and (ii) ice removal is promoted due to low adhesion strength between ice [ 21 , 22 ]. Superhydrophobic coatings on aluminum have demonstrated a remarkable potential to tackle the challenge of icing aircraft surfaces [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A novel approach to target these objectives are micro-textured functional surfaces with icephobic properties. An icephobic surface has per definition the following properties: (i) they delay the solidification time of the water or reduce ice accretion while the heterogeneous nucleation is hindered [ 20 ] and (ii) ice removal is promoted due to low adhesion strength between ice [ 21 , 22 ]. Superhydrophobic coatings on aluminum have demonstrated a remarkable potential to tackle the challenge of icing aircraft surfaces [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, for the first time, Alamri et al [ 14 ] reported on the de-icing behavior of the Direct Laser Interference Patterning of curved aerodynamic profiles, namely airfoils, combined with electrothermal heating used for ice protection systems. After the laser treatment, the airfoil was treated with MecaSurf, a commercial product used to reduce the surface free energy to make it strongly superhydrophobic, with a WCA exceeding 150°, and a roll-off angle < 15.…”
Section: Fabrication Of Superhydrophobic Surfaces With Anti-icing mentioning
confidence: 99%
“…In the latter case, the impact of supercooled water droplets found in clouds, depending on atmospheric conditions, may stick to the surface, creating a dangerous ice layer. Therefore, the overall recommendation of the safety authorities is to strengthen the ice protection systems (IPS) to all commercial aircraft [ 14 ]. These protection systems can be classified into two groups: anti-icing systems, which aim to prevent ice formation, and de-icing systems, which aim at the removal of already-accumulated ice or frost from a surface.…”
Section: Introductionmentioning
confidence: 99%
“…Humans often turn to nature for inspiration when developing new technologies. The lotus leaf, which provided a template for researchers studying superhydrophobic surfaces, is a classic example and has been referenced in many applied studies on superhydrophobicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The superhydrophobic surface property is determined by the contact angle.…”
Section: Introductionmentioning
confidence: 99%